2017
DOI: 10.1007/s41513-017-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Variability of growth pattern observed in Metoposaurus krasiejowensis humeri and its biological meaning

Abstract: Purpose Histological studies on temnospondyl amphibian bones remain rare. A systematic revision of the histology was applied for the purpose of testing the histovariability in the humeri and becoming new information about the growth pattern. Methods The present study includes 12 humeri of Metoposaurus krasiejowensis, which originate from the Late Triassic clay pit near Krasiejów, southwestern Poland. The specimens were scanned with a microCT and the histological thin-sections have been obtained with the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…To test whether or not FEA models and histological results provided similar predictions of cranial mechanical behaviour under feeding loads, the present paper compares results from both methods for a well-known taxon. The early tetrapod Metoposaurus krasiejowensis ( Sulej, 2002 ) (Metoposauridae, Temnospondyli) from the Upper Triassic of southwest Poland provides an interesting case study in view of the great number of excellently preserved specimens recovered as well as the extensive data set for this taxon ( Sulej, 2002 ; Sulej, 2007 ; Barycka, 2007 ; Konietzko-Meier & Klein, 2013 ; Konietzko-Meier & Sander, 2013 ; Gruntmejer, Konietzko-Meier & Bodzioch, 2016 ; Fortuny, Marcè-Noguè & Konietzko-Meier, 2017 ; Teschner, Sander & Konietzko-Meier, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To test whether or not FEA models and histological results provided similar predictions of cranial mechanical behaviour under feeding loads, the present paper compares results from both methods for a well-known taxon. The early tetrapod Metoposaurus krasiejowensis ( Sulej, 2002 ) (Metoposauridae, Temnospondyli) from the Upper Triassic of southwest Poland provides an interesting case study in view of the great number of excellently preserved specimens recovered as well as the extensive data set for this taxon ( Sulej, 2002 ; Sulej, 2007 ; Barycka, 2007 ; Konietzko-Meier & Klein, 2013 ; Konietzko-Meier & Sander, 2013 ; Gruntmejer, Konietzko-Meier & Bodzioch, 2016 ; Fortuny, Marcè-Noguè & Konietzko-Meier, 2017 ; Teschner, Sander & Konietzko-Meier, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous histological studies on the humerus of temnospondyls (Figure 1) have shown a great diversity of bone patterns with a large range of cortical vascular densities and growth rates (de Ricqlès, 1979Ricqlès, , 1981Steyer et al, 2004;Laurin et al, 2006;Witzmann, 2009;Mukherjee et al, 2010;Sanchez et al, 2010a,b;Konietzko-Meier and Klein, 2013;Konietzko-Meier and Sander, 2013;Sanchez and Schoch, 2013;McHugh, 2014;Canoville and Chinsamy, 2015;Teschner et al, 2018). This histodiversity partly results from a significant size variability and wide range of temnospondyl lifestyles (Schoch, 2009(Schoch, , 2014Sanchez et al, 2010b).…”
Section: Evolution Of Limb Bone Growth In Non-amniotic Tetrapodsmentioning
confidence: 94%
“…The dimorphic character of clavicles described herein and the two growth patterns of dermal and long 362 bones (humeri) (Teschner, Sander & Konietzko-Meier, 2017) suggest that the ontogeny of specimens 363 assigned to Metoposaurus krasiejowensis could have proceeded via a different growth rate and time 364 span of metamorphosis, caused by differing environmental conditions. The similar number of specimens 365 from both populations (Tc1/Tc2 -44%/56% and Ts1/Ts2 -53%/47%) suggests stable populations.…”
mentioning
confidence: 88%